GOOD GOVERNANCE OF KOPERASI WANITA SERBA USAHA â€œSETIA BUDI WANITAâ€ JAWA TIMUR - Puspitasari, Devy Sylvia; Ludigdo, Unti (Jurnal Ilmiah Mahasiswa FEB, 2013)
This research was conducted to understand the implementation of good governance on Koperasi Wanita Serba UsahaÂ  â€œSetia Budi Wanitaâ€Â  Jawa Timur. Cooperative is economic organization that based on sense of family. Womenâ€™s Cooperative in the present society with the purpose to achieve the welfare of members and society with profesionalism, independent woman, qualified and integrity. This type of researchÂ  isÂ  aÂ  qualitative descriptive method. Instruments used in data collection are interviews, observation, and documentation.Â  The results of the research represent passage of the good governance principles includes of transparencyÂ  in the provisioningÂ  informationÂ  for administrators, employees, PPL, PJ, members in a transparent and opened, so that everyÂ  employeeÂ  alreadyÂ  knowsÂ  how theÂ  systemÂ  that are withinÂ  the cooperative principleÂ  accountibility.Â  While,Â  the principleÂ  ofÂ  responsibilityÂ  shownÂ  SBW towards employees by providing a range of benefits, health insurance, safety and social responsibilityÂ  to theÂ  society. ThenÂ  the principle ofÂ  independencyÂ  showed nothing intervention from the internal, but external side there is a little ideological andÂ  philosophicalÂ  differencesÂ  cooperative.Â  Finally, theÂ  FairnessÂ  principle, shareholders (members) receive equal and fair treatment in the implementation of the RAT and the division SHU, stakeholders of the employees who were recruited based on their expertise, so the company does not discriminate against employees based on racial and establish a system of reward and punishment is fair. Key Word : Cooperative, Good Governance